(untitled) (Journal on Excellence in College Teaching, 2024)
With the success of simulations like Reacting to the Past, role-playing games have seen increased usage in educational settings. This study examined the use of an original role-playing game in four political theory classes. It measured outcomes of student perception and success in regard to learning objectives asking students to understand, apply, and evaluate the arguments of political theorists. The findings indicate that within a role-playing political theory class, students who knew their assigned philosopher well enough to reference him or her on the final exam scored higher than students who avoided discussing their theorist. Additionally, final exam scores were higher in classes that made use of role playing compared to those in a control group.